Regulatory framework on bioequivalence criteria for locally acting gastrointestinal drugs: the case for oral modified release mesalamine formulations. Issue 9 (2nd September 2017) - Sferrazza, Gianluca; Siviero, Paolo D; Nicotera, Giuseppe; Turella, Paola; Serafino, Annalucia; Blandizzi, Corrado; Pierimarchi, Pasquale
ABSTRACT: Introduction : Bioequivalence testing for locally acting gastrointestinal drugs is a challenging issue for both regulatory authorities and pharmaceutical industries. The international regulatory framework has been characterized by the lack of specific bioequivalence tests that has generated a negative impact on the market competition and drug use in clinical practice. Areas covered : This review article provides an overview of the European Union and United States regulatory frameworks on bioequivalence criteria for locally acting gastrointestinal drugs, also discussing the most prominent scientific issues and advances that has been made in this field. A focus on oral modified release mesalamine formulations will be also provided, with practical examples of the regulatory pathways followed by pharmaceutical companies to determine bioequivalence. Expert commentary : The development of a scientific rationale to demonstrate bioequivalence in this field has been complex and often associated with uncertainties related to scientific and regulatory aspects. Only in recent years, thanks to advanced knowledge in this field, the criteria for bioequivalence assessment are undergoing substantial changes. This new scenario will likely result in a significant impact on pharmaceutical companies, promoting more competition through a clearer regulatory approach, conceived for streamlining the demonstration of therapeutic equivalence for locally acting gastrointestinal drugs.